PERLOCUTIONARY ACT OF THE CENTRAL CHARACTER UTTERANCES THAT SIGNIFIES GENDER DISCRIMINATION IN ANNE WITH AN E SERIES SEASON ONE (2017) - Sherin Julya Andini Nova; Sari Rejeki; Agnes Setyowati (Journal Albion : Journal of English Literature, Language, and Culture, 2022)
This study analyses the perlocutionary effect of the central character’s utterances that signifies gender-based discrimination in Anne with an E series season one (2017). This study uses descriptive-qualitative method. By using Austin and Searle’s theory on Speech Act and a feminist perspective, the perlocutionary act is analysed through the analysis of type, form and function of utterances. The results of the study indicate that there is resistance and disapproval of gender discrimination. From the central character’s utterances, 3 forms of gender discrimination were identified, namely marginalization, stereotype and subordination.Keywords:perlocutionary act ;speech act; Anne with an E series; gender discrimination.